Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada L'amore Cafe Di Denpasar - yuliastina, ni kadek; Jatra, Ni Made (E-Jurnal Manajemen, 2014)
This study was to determine the effect of service quality consists of physical evidence, reliability, responsiveness, assurance and empathy simultaneously and partially on customer satisfaction in L'amore Cafe in. The research was conducted in L’amore cafe Denpasar, which is located at Jalan Tukad Barito No 18A Denpasar. The data was collected by interview and questionnaire. The samples used were 105 respondents based on purposive sampling with data analysis technique of multiple linear regression.The conclusion that: quality simultaneous services significantly influence customer satisfaction in L'amore cafe in Denpasar and partially that the quality of the service and a significant positive effect on customer satisfaction in L'amore cafe in Denpasar   Keywords: service quality, customer satisfaction
Keywords: service quality, customer satisfaction